PENGABDIAN MASYARAKAT SOCIAL EDUCATION ‘’ANTI BULLYING’’ DI SMA HASANUDIN - Rosa Nur Fatmawati; Ibnu Eka Nugroho Jati; Diyah Ayu Widyaningrum; Mukarom Mukarom (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2023)
Bullying is behavior that intentionally wants to dominate, hurt, or get rid of the victim, either directly (physically) or indirectly (verbally). The impact of bullying can cause psychological pressure and if left untreated will worsen the victim to commit suicide. This study aims to determine the most appropriate types of interventions that can be implemented to reduce bullying and prevent suicide risk using a systematic review based on PRISMA guidelines. The studies were searched across five databases: Scopus, ScienceDirect, Proquest, Pubmed and CINHL and must have been published from 2014-2019. Articles are identified using the keywords